2018
DOI: 10.1371/journal.pone.0199632
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix surface regulates self-assembly of three-dimensional placental trophoblast spheroids

Abstract: The incorporation of the extracellular matrix (ECM) is essential for generating in vitro models that truly represent the microarchitecture found in human tissues. However, the cell-cell and cell-ECM interactions in vitro remains poorly understood in placental trophoblast biology. We investigated the effects of varying the surface properties (surface thickness and stiffness) of two ECMs, collagen I and Matrigel, on placental trophoblast cell morphology, viability, proliferation, and expression of markers involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 55 publications
0
32
0
1
Order By: Relevance
“…Accumulating evidence in other organ systems and cancer models suggest that culturing cells in three-dimensions (3D) can provide more anatomically- and physiologically-relevant results compared to traditional 2D monolayer cultures 7 . While some researchers have begun to culture placental cells as 3D spheroids or organoids 812 , our overall understanding of the transcriptomic changes and functional outcomes associated with its formation remains preliminary. Characterization studies contrasting novel 3D spheroids against 2D monolayers are especially lacking – yet, these are necessary to justify its use and advancement, as the theorized advantages ( e .…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence in other organ systems and cancer models suggest that culturing cells in three-dimensions (3D) can provide more anatomically- and physiologically-relevant results compared to traditional 2D monolayer cultures 7 . While some researchers have begun to culture placental cells as 3D spheroids or organoids 812 , our overall understanding of the transcriptomic changes and functional outcomes associated with its formation remains preliminary. Characterization studies contrasting novel 3D spheroids against 2D monolayers are especially lacking – yet, these are necessary to justify its use and advancement, as the theorized advantages ( e .…”
Section: Introductionmentioning
confidence: 99%
“…Tissue stiffness is now well-established as a critically important regulator of a wide variety of cellular processes, including differentiation 23 and disease progression 24 ; but the role of extracellular tissue mechanics on trophoblast fusion has not previously been defined. Recent studies have demonstrated that ECM thickness affects fusion-related markers of mRNA and secreted proteins in trophoblasts 25 suggesting that mechanics may play a role, but whether trophoblast fusion is mechanically sensitive to disease-specific physiological cues remains undefined. Interestingly, recent evidence from in vivo imaging studies demonstrates that tissue stiffness varies significantly across patients diagnosed with pregnancy complications, including preeclampsia [26][27][28] , intra-uterine growth restriction 29 , and gestational diabetes mellitus 30 compared to normal placental tissue 26 (literature values presented in Fig.…”
mentioning
confidence: 99%
“…Pioneer work on placental spheroids from, for example, immortalized EVTs, trophoblast Jar cell line, and the choriocarcinoma cell line BeWo have been used as 3D models to study aspects of human placental development in vitro [135][136][137] and, when co-cultured with human immortalized endometrial stromal cell lines, have served as a model for TB invasiveness [138,139]. Moreover, attempts have been performed to develop 3D models for human endometrial cells that could also be used to investigate endometrial cancer [140][141][142].…”
Section: Stem Cells For Human Placental Development and Organoidsmentioning
confidence: 99%